Nucleotide-Binding Oligomerization Domain 1/Toll-Like Receptor 4 Co-Engagement Promotes Non-Specific Immune Response Against K562 Cancer Cells - Guzelj, Samo; Jakopin, Žiga (Frontiers in Pharmacology, 2022)
Nucleotide-binding oligomerization domain 1 (NOD1) receptor and Toll-like receptor 4 (TLR4) belong to the family of pattern recognition receptors. Interactions between these receptors profoundly shape the innate immune responses. We previously demonstrated that co-stimulation of peripheral blood mononuclear cells (PBMCs) with D-glutamyl-meso-diaminopimelic acid (iE-DAP)-based NOD1 agonists and lipopolysaccharide (LPS), a TLR4 agonist, synergistically increased the cytokine production. Herein, we postulate that stimulation of NOD1 alone or a combined stimulation of NOD1 and TLR4 could also strengthen PBMC-mediated cytotoxicity against cancer cells. Initially, an in-house library of iE-DAP analogs was screened for NOD1 agonist activity to establish their potency in HEK-Blue NOD1 cells. Next, we showed that our most potent NOD1 agonist SZZ-38 markedly enhanced the LPS-induced cytokine secretion from PBMCs, in addition to PBMC- and natural killer (NK) cell-mediated killing of K562 cancer cells. Activation marker analysis revealed that the frequencies of CD69+, CD107a+, and IFN-γ+ NK cells are significantly upregulated following NOD1/TLR4 co-stimulation. Of note, SZZ-38 also enhanced the IFN-γ-induced PBMC cytotoxicity. Overall, our findings provide further insight into how co-engagement of two pathways boosts the non-specific immune response and attest to the importance of such interplay between NOD1 and TLR4.